MAKING STUDENTS WITH VISUAL IMPAIRMENT’S RIGHT TO ACCESS TEXTBOOKS REAL: THE ROLE OF MINISTRY OF EDUCATION IN PUBLISHERS’ VIEWS - Issavara Sirirungruang (Proceedings of International Conference on Special Education, 2015)
Access to textbooks in accessible format is one of the important barriers generations of students with visual impairment in Thailand face in their education. The purpose of this paper is to present a part of findings yielded from the study of students with visual impairment’s right to access textbooks in the perspective of publishers who are copyright owners. The main question was what are the essential factor to make students with visual impairment’s right to access textbooks real. A semi-structure interview was employed to inquire administrators from four major publishers who are approved by the Ministry of Education to produce and sell textbooks under the national curriculum to schools nationwide. Results showed that in the views of publishers, the Ministry of Education is the important stakeholder to make the right to access textbooks of students with visual impairment real. Publishers are ready to collaborate provided that the Ministry of Education issues a clear policy to deal with the textbooks electronic files. Moreover, the Ministry of Education should initiate the establishment of a central centre/organization to reproduce, store and distribute textbooks of publishers to students with visual impairment. People may consider that publishers who are copyright owners are the important factors to make the right to access textbooks real for students with visual impairment. However, findings of this study indicate that in order to mobilize this issue Ministry of Education needs to take responsibilities. We will not achieve inclusive education for all children if students with visual impairment still being left unable to access their textbooks just as other sighted peers.